EFFECT OF PLYOMETRIC TRAINING WITH AND WITHOUT YOGIC PRACTICES ON SKILL PERFORMANCE VARIABLE OF WOMEN CRICKET PLAYERS - Gayatri, C; Rambabu, D.; Sarojini, G Sarah (ShodhKosh: Journal of Visual and Performing Arts, 2024)
To find out the Effect of Plyometric training with and without Yogic Practices on Skill Performance variable of Women Cricket players. To achieve the above purpose of the study Ninety (90) Ninety Intercollegiate level Cricket players, ages 18 to 22, were randomly selected from Chittoor District for the current inquiry. The total strength will be dividing into 3 different training groups of 30 players each. Using a genuine random group design, the research includes a pre- and posttests. Ninety participants are divided into three equal groups, each with thirty Female Cricket Players. Experiment Group-I, Experiment Group-II, and Control Group-III. Plyometric Training combined with Yogic Practices are the focus of Experimental Group I, whereas Plyometric Training alone is the focus of Experimental Group II, which serves as a Control Group. This group receives no additional attention other than their usual warm-up. The Researcher conduct pre-tests on Skill Performance of all the participants in this study. For 12 weeks, the experimental groups will undergo their separate training regimens. After 12-week trial period, all three groups will be subjected to post-tests on the dependent variable of Batting skill in cricket. The experimental treatment was thought to have an impact if the beginning and end mean values of certain variables differed. For each variable, the statistical method Analysis of Covariance (ANCOVA) was performed to assess its significance.